2011
DOI: 10.1038/mt.2011.34
|View full text |Cite
|
Sign up to set email alerts
|

Correction of Neurological Disease of Mucopolysaccharidosis IIIB in Adult Mice by rAAV9 Trans-Blood–Brain Barrier Gene Delivery

Abstract: The greatest challenge in developing therapies for mucopolysaccharidosis (MPS) IIIB is to achieve efficient central nervous system (CNS) delivery across the blood-brain barrier (BBB). In this study, we used the novel ability of adeno-associated virus serotype 9 (AAV9) to cross the BBB from the vasculature to achieve long-term global CNS, and widespread somatic restoration of α-N-acetylglucosaminidase (NAGLU) activity. A single intravenous (IV) injection of rAAV9-CMV-hNAGLU, without extraneous treatment to disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 47 publications
7
142
3
Order By: Relevance
“…Numerous preclinical studies with gene replacement by in vivo intracranial AAV administration have shown partial to complete phenotypic correction in animal models of several LSDs. These include MPS I (Hinderer et al, 2014), MPS IIIA (Ruzo et al, 2012), MPS IIIB (Fu et al, 2011), MPS VII (Cearley and Wolfe, 2007), MLD (Miyake et al, 2014; Sevin et al, 2006), multiple sulfatase deficiency (MSD) (Spampanato et al, 2011), Niemann-Pick A disease (Passini et al, 2005), Pompe disease (Falk et al, 2013), GM1-gangliosidosis (Weismann et al, 2015), Tay Sachs disease (Cachón-González et al, 2006) and Sandhoff disease (Sargeant et al, 2011). …”
Section: Different Modalities For Different Diseasesmentioning
confidence: 99%
“…Numerous preclinical studies with gene replacement by in vivo intracranial AAV administration have shown partial to complete phenotypic correction in animal models of several LSDs. These include MPS I (Hinderer et al, 2014), MPS IIIA (Ruzo et al, 2012), MPS IIIB (Fu et al, 2011), MPS VII (Cearley and Wolfe, 2007), MLD (Miyake et al, 2014; Sevin et al, 2006), multiple sulfatase deficiency (MSD) (Spampanato et al, 2011), Niemann-Pick A disease (Passini et al, 2005), Pompe disease (Falk et al, 2013), GM1-gangliosidosis (Weismann et al, 2015), Tay Sachs disease (Cachón-González et al, 2006) and Sandhoff disease (Sargeant et al, 2011). …”
Section: Different Modalities For Different Diseasesmentioning
confidence: 99%
“…Self-complementary rAAV vectors can significantly improve the efficacy of transduction as compared with identical vectors in a single-stranded format [59-61] . Widespread and high expression of transgenes in the brain has been reported by systemic intravenous injection of rAAV9 [62], intraparenchymal injection of rAAV9 into nuclei with divergent connections [49], and their combinations [63]. These strategies for improved gene therapy should be exploited in future.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that systemic delivery of rAAV8 or rAAV9 containing the deficient gene cause elevation of lysosomal enzyme activity in CNS lesions and correction of disease progression in mouse models of MPS IIIA [9093] and MPS IIIB [82,9496]. Fu et al showed that a single IV administration of a scAAV9 vector encoding human N-sulfoglucosamine sulfohydrolase (hSGSH) (5e 12 vg/kg) in an MPS IIIA model mouse significantly improved behavior performance and survival rate [93] Improvements were best when the vector was administered at an early stage of disease, but these phenotypes were also partially corrected when treatment was delayed until mice showed intermediate progression of disease.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%
“…These results suggest that scAAV9-hSGSH vector may be clinically useful to reverse disease progression in patients with established MPS IIIA. This group also showed that IV administration of rAAV9 containing human α- N -acetylglucosaminidase (hNAGLU) corrected GAG accumulation in CNS and somatic tissues and provided long-term (> 18 months) neurological improvement in MPS IIIB model mouse [94]. An investigational new drug (IND)-enabling good laboratory practice (GLP)-compliant toxicology study demonstrated that injection of the rAAV9 did not provide adverse clinical events and chronic toxicity during a 6-month study [95].…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%